Kecemasan dalam Menghadapi Assessment Centre di Kalangan Pekerja Telekomunikasi - Zulkarnain, Zulkarnain; R. Pohan, Vivi Gusrini; Sulistyawati, Endang (Jurnal Psikologi, 2015)
The purposeof thisstudy wasto examine the employee’s anxiety in facing assessment centers based on the big fivepersonality and perceptions of organizational support. The subjects of this studywere 241 telecommunication employees with position sequel to assistant manager. Data were collected using assessment centre anxiety scale, big five inventory and organizational support scale. The statistic a analysis showed that assessment centre anxiety was negatively related to the trait of extraversion, openness to experience, and organizational support and positively to neuroticism and conscientiousness. The implication of this study is that the role of organizational support is crucial in improving employee’s conviction and confidence in facing assessment centre.